Islam and the Limits of the State Reconfigurations of Practice, Community and Authority in Contemporary Aceh - Feener, R. Michael; Kloos, David; Samuels, Annemarie (Leiden Studies in Islam and Society, 2015)
This book examines the complex relationships between the state state implementation of Shariʿa and diverse lived realities of everyday Islam in contemporary Aceh, Indonesia. ; Readership: Students and scholars concerned with the topics of state Islamic Studies, Law and Society, and the Anthropology of Islam, as well as broader circles of scholars and development practitioners interested in social and religious transformations in post-disaster/post-conflict Aceh, Indonesia.